If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -91 = -27 + 12b + -16 Reorder the terms: -91 = -27 + -16 + 12b Combine like terms: -27 + -16 = -43 -91 = -43 + 12b Solving -91 = -43 + 12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12b' to each side of the equation. -91 + -12b = -43 + 12b + -12b Combine like terms: 12b + -12b = 0 -91 + -12b = -43 + 0 -91 + -12b = -43 Add '91' to each side of the equation. -91 + 91 + -12b = -43 + 91 Combine like terms: -91 + 91 = 0 0 + -12b = -43 + 91 -12b = -43 + 91 Combine like terms: -43 + 91 = 48 -12b = 48 Divide each side by '-12'. b = -4 Simplifying b = -4
| X=3/5y-15 | | .333B+.333B+B=1 | | y=-17/2(x-20)+60 | | .1A+.4B+C=0 | | 2(-3)-3=-3 | | .9A-.3B=0 | | .9A-.4B=0 | | 8-2x=4x-16 | | 6x=1/3y-4 | | 24/(2x-1)=72/(2x+1) | | 1/3x^2+1/2x-8=0 | | 1/3x+1=5 | | 4x^3/4-500=0 | | 7-2q=41 | | 15/3+8 | | 2/3x-1/6=5/6 | | f(x)=-9x^2+5x+4 | | x/3+8=x/15 | | -3x=5y-10 | | 7m^2+6=-9 | | x^2-(8/9)x-64/81 | | 5/8x+9/8=-1 | | 5=3+4x | | f(x)=-x^2-11 | | (x^2-36)/3x | | 3x+3+2x=1+5x+3 | | 5x^2+x=-19x | | X-19/x=0.98 | | -3(p-7)=36 | | 11x=-4x+30 | | 9p=-9p+18 | | 5a=-7a+36 |